Lampa'ra Enterprise : USB light socket / Nur Aqilah Zaidi … [et al.] - Zaidi, Nur Aqilah; Amin, Nur Allisa Sabrina; Kamal, Norsahida; Kamarudin, Nur Ain Shafizan; Abul Halim, Wan Abdul Aziz (2017)
Lampa'ra Enterprise is producing a new product that convenient to users which is USB Lamp Socket . It is a light bulb adapter that adds a USB charging port, plus an On/Off switch, to any lamp you have got. Many of us have multiple gadgets and devices that needs to be charge consistently. People always has a problem when their devices running out of power. Usually, power source are placed on either behind heavy sofa, bed or across the room. Never close and easy when you need it even now. Besides, a standard chargers have short cables that make them more frustrating to use. This product is very convenient because the product dimensions (2.7 x 2.7 x 2.6 inches) , weight (0.119 pounds) and it consist of 2 AMP Rapid Charging USB port. It shows that this product is very suitable for those people that always with their gadgets. It is design specifically for table lamp which is perfect whether at home or office, even for traveler also can use it. It is provide on/off switch controls lamp and 2 AMP USB charging port. Even the lamp is switch off the charger are still charge your device as long as it connected to the power source. Simply remove your existing light bulb, screw in the USB lamp Socket, then replace the bulb. Get a USB Lamp Socket for every lamp in your home and always be within reach of power.